2016
DOI: 10.1007/s11274-016-2072-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between superficial and solid-state cultures of Isaria fumosorosea: conidial yields, quality and sensitivity to oxidant conditions

Abstract: Conidia production and quality from mycoinsecticides in solid-state cultures (SSC) are frequently inferred from superficial culture (SC) results. Both parameters were evaluated for two Isaria fumosorosea strains (ARSEF 3302 and CNRCB1), in SC and SSC, using culture media with the same chemical composition. For both strains, conidia production was higher in SC than SSC in terms of conidia per gram of dry substrate. Germination in both strains did not show significant differences between SC and SSC (>90 %). Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 41 publications
0
7
0
14
Order By: Relevance
“…SSF is an aerobic process, therefore is highly needed an adequate oxygen diffusion through the fermented matter making one of the most important phenomena to support the microbial development [20]. Commonly a passive oxygen diffusion takes place in reactors such as flasks, trays or bags resulting in a high production of spores [14,16,21]. Arzumanov et al [22] reported that the aeration does not always make a big difference to increase the production of spores.…”
mentioning
confidence: 99%
“…SSF is an aerobic process, therefore is highly needed an adequate oxygen diffusion through the fermented matter making one of the most important phenomena to support the microbial development [20]. Commonly a passive oxygen diffusion takes place in reactors such as flasks, trays or bags resulting in a high production of spores [14,16,21]. Arzumanov et al [22] reported that the aeration does not always make a big difference to increase the production of spores.…”
mentioning
confidence: 99%
“…All strains were maintained in Sabouraud agar plugs with 1 ml of sterile water at 4°C. Inocula were obtained by placing an agar plug in oat flour agar medium (Tlecuitl-Beristain et al 2010) and incubating for 10 days at 28°C with photoperiod of 12 h light and 12 h dark (Muñiz-Paredes et al 2016). Conidia were harvested using a magnetic stirrer with 20 ml of 0Á05% Tween 80.…”
Section: Resultsmentioning
confidence: 99%
“…Conidia were harvested using a magnetic stirrer with 20 ml of 0·05% Tween 80. Conidial suspensions were filtered through four layers of cheesecloth, and conidia production was determined using a Neubauer chamber (Muñiz‐Paredes et al ). Dilutions were done when necessary and 10 µl of the conidial suspension were loaded in each side of the chamber.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations